Analyzing the Parameters of the Coal—Gas System Using a Low-Cost Device Based on a Flowmeter - Norbert Skoczylas (Adsorption Science & Technology)
Investigations of the coal—gas system—in particular, those concerning the amount of the gas adsorbed and the kinetics of its release—are extremely important in the analysis of hazards associated with the presence of methane and outbursts of gas and rocks. Such an investigation is also useful for analyzing the adsorbent parameters. Adsorption analyzers that are available on the market fall into two types: gravimetric and volumetric. Gravimetric analyzers are very complex, stationary devices. Their biggest drawback is the problem pertaining to a sudden pressure change, which initiates the processes of gas adsorption and transportation. This is associated with a higher degree of measurement uncertainty with regard to the determination of the diffusion coefficient. By contrast, volumetric analyzers are usually far cheaper and are capable of processing sudden pressure changes. However, in this case, the measurement is seldom isobaric in nature, which makes it difficult to use for determination of the diffusion coefficient on the basis of the unipore model. The author of this paper intends to show a simple device based on a gas flowmeter, which makes use of a phenomenon known as ‘barbotage’. The cost of constructing such a device is several dozen times cheaper than the cost of gravimetric and volumetric analyzers available on the market. A sudden pressure change is allowed, and the release of methane is measured under quasi-isobaric conditions. The paper discusses the concept of the device and provides an analysis of the results that it generated. These results were juxtaposed with those obtained using a gravimetric reference device.